1997
DOI: 10.1007/bf03157997
|View full text |Cite
|
Sign up to set email alerts
|

Generalized Rarita-Schwinger equations for non-strange baryons

Abstract: The Rarita-Schwinger equations are generalised for the delta baryon having spin 3/2 and isospin 3/2. The coupling of the nucleon and the delta fields is studied. A possible generalisation of the Walecka model is proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2000
2000
2000
2000

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
1
0
0
Order By: Relevance
“…Similar arguments have been presented in Ref. [17] where the authors identified the sigma field in the Walecka model with the degrees of freedom associated with the ∆(1232) in the context of quantum hadrodynamics. However, we repeat that -as opposed to a Lagrangian leading to BR scaling [1] -our effective meson-sobar Lagrangian is not invariant under scale transformation symmetry.…”
Section: B Relation To Br Scalingsupporting
confidence: 76%
“…Similar arguments have been presented in Ref. [17] where the authors identified the sigma field in the Walecka model with the degrees of freedom associated with the ∆(1232) in the context of quantum hadrodynamics. However, we repeat that -as opposed to a Lagrangian leading to BR scaling [1] -our effective meson-sobar Lagrangian is not invariant under scale transformation symmetry.…”
Section: B Relation To Br Scalingsupporting
confidence: 76%